Comprehensive model for the thermoelectric properties of two-dimensional carbon nanotube networks - Dash, Aditya; Scheunemann, Dorothea; Kemerink, Martijn (Physical review applied, 2022)
Networks of semiconducting single-walled carbon nanotubes (SWCNTs) are interesting thermoelectric materials due to the interplay between CNT and network properties. Here, we present a unified model to explain charge and energy transport in SWCNT networks. We use the steady-state master equation for the random resistor network containing both intra- and intertube resistances, as defined through their one-dimensional density of states that are modulated by static Gaussian disorder. The tube-resistance dependence on the carrier density and disorder is described through the Landauer formalism. Electrical and thermoelectric properties of the network are obtained by solving Kirchhoff’s laws through a modified nodal analysis, where we use the Boltzmann-transport formalism to obtain the conductivity, Seebeck coefficient, and electronic contribution to the thermal conductivity. The model provides a consistent description of a wide range of previously published experimental data for temperature and charge-carrier-density-dependent conductivities and Seebeck coefficients, with energetic disorder being the main factor to explain the experimentally observed mobility upswing with carrier concentration. Moreover, we show that, for lower disorder energies, the Lorentz factor obtained from the simulation is in accordance with the Wiedemann-Franz law for degenerate-band semiconductors. At higher disorder, deviations from simple band behavior are found. Suppressed disorder energy and lattice thermal conductivity can be the key to higher thermoelectric figures of merit, zT, in SWCNT networks, possibly approaching or even exceeding zT = 1. The general understanding of transport phenomena will help the selection of chirality, composition, and charge-carrier density of SWCNT networks to improve their efficiency of thermoelectric energy conversion.
Gesehen am 25.01.2023